Odnos študentov zdravstvene nege do hudo bolnih, umirajočih in evtanazije - Trupi, Matjaž (Obzornik zdravstvene nege, 2007)
The article presents attitudes of the students of nursing care towards terminally ill and dying and on palliative health and nursing care. The results of the inquiry among the students of the third year of nursing care onthe High School of Nursing in Ljubljana on terminally ill and dying patientsand on their attitude towards euthanasia are presented. 50 students were included in the study. All of them are support the idea of palliative nursing care, while their attitudes towards euthanasia differ. The majority ofthem do not support the idea of euthanasia because of the possibility of abuse. The study also revealed that the majority of the students feel they do not get enough knowledge on the work with the dying. The results of the inquiry also reveal that the students lack specific knowledge which would enable them to state their argument in favor or against palliative nursing care and euthanasiač in future, more subjects concerning nursing care of the terminally ill and palliative nursing care should be included in the teaching program. Students should also be enticed to think and discuss these problems more often.
Keywords: euthanasia; evtanazija; paliativna oskrba; student; študenti; umiranje; zdravstvena nega